A symmetric and a transposition cipher using the Euler’s totient function - A. P. Madushani (Ceylon Journal of Science, 2019)
Cryptography provides a method of exchanging sensitive information in a secured form while assuring its confidentiality. Encryption and decryption are the two steps in which the process gets completed. In the present work, we introduce two algorithms using modular arithmetic and ASCII symbols to encrypt and decrypt messages. Our schemes are based on symmetric ciphers, in which a secret key is exchanged between the sender and the receiver for the encoding and decoding process to take place.